Fair Use Provisions under the Indian Copyright Act: Awareness Among Librarians of Colleges and Universities in Maharashtra (Journal of Intellectual Property Rights (JIPR), 2023)
Indian Copyright Act, 1957 provides a private right in copyright which extensively deals with provisions that guaranteeaccess to knowledge as well. Copyright is an exclusive and assignable legal right given to the author for a particular periodfor original literary, dramatic, artistic works, and musical work whether published or unpublished. These rights are notabsolute but subject to restrictions and limitations imposed by law. Section 52 of the Copyright Act, 1957 is one suchprovision that restraints the exclusive enjoyment of rights given to the copyright holder. As per Section 52 (1)(o) of theCopyright Act, 1957 a non-commercial library is permitted/allowed to make three copies of a book for library use, providedsuch books are not available for sale in India. The present article is about the concept of fair dealing which is originatedfrom the Common of laws of England. Although, the concept of fair use and fair dealing are used synonymously, the IndianCopyright Act, 1957 deals with fair dealing under Section 52 of the Copyright Act, 1957. The reproductions of works forresearch or private study, taking photocopy for research and educational purpose, etc., are covered under the doctrine of fairuse. This paper will explain the conceptual framework of the Indian Copyright Act and the empirical reality in libraries ofMaharashtra. It attempts to empirically test the usage of fair use provisions under the Indian Copyright Act and theawareness among librarians of Colleges and Universities in Maharashtra. The research methodology used for the presentstudy is both doctrinal and non-doctrinal. It was observed that most of the librarians are aware of Copyright Law andcopyright exceptions but when it comes to the implementation librarians also face difficulty and it leads to the infringementof copyright.